The Effect of Principal Leadership and Organisational Culture on Teacher Performance through Work Discipline as an Intervening Variable (A Case Study of Senior High Schools in Berastagi District) - Simanjuntak, Nia Dewanti; Pramono, Suwito Eko; Widiyanto, Widiyanto (PT FORMOSA CENDEKIA GLOBAL, 2026)
This study analyses the influence of principal leadership and organisational culture on teacher performance, with work discipline as an intervening variable, in high schools across the Berastagi District. A quantitative approach with an ex post facto design was employed, utilising path analysis to examine the structural relationships between variables. The research involved a sample of 122 teachers selected from a population of 175 through simple random sampling. Data were collected using Likert scale questionnaires that were rigorously tested for validity and reliability. The findings reveal that principal leadership has a significant positive effect on both work discipline and teacher performance. While organisational culture significantly affects work discipline, it had a non-significant negative direct effect on teacher performance. Crucially, the analysis demonstrates that work discipline significantly mediates the influence of principal leadership and organisational culture on teacher performance. This indicates that discipline serves as the primary